Bob Crow: socialist, leader, fighter : a political biography - Gall, Gregor (Manchester University Press, 2017)
Bob Crow was the most well-known and most militant union leader of his generation. This biography examines his leadership of the RMT union, examining and exposing a number of popular myths created about him by political opponents. Using the schema of his personal characteristics (including his public persona), his politics and the power of his members, it explains how and why he was able to punch above his weight in industrial relations and on the political stage, helping the small RMT union become as influential as many of its much larger counterparts. As RMT leader, he oversaw a rise in membership, a more assertive and successful bargaining approach, and led the realignment of radical left politics in response to the hegemony of 'new' Labour. While he failed to unite all socialists into one new party, he established himself as the leading popular critic of neo-liberalism, 'new' Labour and the age of austerity.